Optimized output-based input shaping for control of single-link flexible manipulator using linear matrix inequality - Nura Musa Tahir; Mustapha Muhammad; Bashir Bala Muhammad; Haliru Liman; Aminu Yahaya Zimit; Auwal Shehu Tijjani (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Precise hub angle positioning due to tip deflections, flexible motions and under various payloads is enormous tasks in the control of single-link flexible manipulators. In this paper, output-based command shaping (OBCS) was designed using the system output for tip deflections and residuals vibrations suppression, and this was incorporated with a linear matrix inequality (LMI) closed-loop control scheme for precise hub angle positioning.  The robustness of the hybrid control scheme was tested by changing the payloads from 0g to 30g, and 50g. Simulation results showed that endpoint residuals vibrations and tip deflections due to flexible motions were suppressed and hence precise hub angle positioning under various payloads was achieved. Integral absolute error (IAE), integral square error (ISE) and time response analysis (TRA) were used as the performance indexes. Hence, the hybrid control scheme is simple and robust.